Efficacy of combined transarterial radioembolization and sorafenib in the treatment of hepatocarcinoma: A meta-analysis. Issue 3 (March 2022) - Facciorusso, Antonio; Paolillo, Rosa; Tartaglia, Nicola; Ramai, Daryl; Mohan, Babu P.; Cotsoglou, Christian; Chandan, Saurabh; Ambrosi, Antonio; Bargellini, Irene; Renzulli, Matteo; Sacco, Rodolfo
Abstract: Background: Adjuvant sorafenib may further enhance the efficacy of transarterial radioembolization for the treatment of hepatocellular carcinoma. Aims: To evaluate the efficacy and safety of radioembolization plus sorafenib in hepatocellular carcinoma patients. Methods: With a literature search through October 2020, we identified 9 studies (632 patients). Primary outcome was overall survival. Results were expressed as pooled median, odds ratio, or hazard ratio and 95% confidence intervals. Results: Pooled overall survival after radioembolization plus sorafenib was 10.79 months (95% confidence interval 9.19–12.39) and it was longer in Barcelona Clinic Liver Cancer (BCLC) B (14.47 months, 9.07–19.86) as compared to BCLC C patients (10.22 months, 7.53–12.9). No difference between combined therapy versus radioembolization alone was observed in terms of overall survival (hazard ratio 1.07, 0.89–1.30). Pooled median progression-free survival was 6.32 months (5.68–6.98), with 1-year progression-free survival pooled rate of 38.5% (12.7%-44.2%). No difference in progression-free survival (hazard ratio 0.94, 0.79–1.12) between the two treatments was observed. Pooled rate of severe adverse events was 48.9% (26.7%-71.2%), again with no difference between the two treatment regimens (odds ratio 1.52, 0.15–15.02). Conclusions: The association of sorafenib does not seem to prolong survival nor delay disease progression in patients treated with radioembolization.